Role of information and communication technology in development of instruction ‎and science of nursing from the view point of nursing students at Shahrekord ‎Medical Sciences University - ali dehkordi (Journal of Holistic Nursing and Midwifery)
Introduction: Information and communication technology (ICT), are strengthening ‎technologies used in nursing sciences. Today, people at any part of the world can receive their ‎required information. But no doubt information and communication technologies had their ‎most effect on educational surroundings. Application of ICT on education has led ‎educational surroundings and science development to become directed toward virtualization. ‎This will lead interpersonal communication for development and expansion of sciences to be ‎performed increasingly through computer. With emergence of internet, this medium was ‎employed as a complement for providing information and education.‎